CHANGES IN SOIL PHYSICAL CHARACTERISTICS ON THE SOIL CRUST PROCESS THROUGH THE USE OF CHICKEN MANURE AND POLYACRYLE AMIDE UNDER INTENSE RAINFALL - Oteng Haridjaja (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2019)
Soil crust is a soil suface layer which is more compact, harder, and brittle when it is drier than underlaying material. The soil physical characteristics such as aggregate stability, bulk density and soil permeability rate are closely related to this soil crust process. An experiment was conducted to evaluate the effects of chicken manure doses and certain chicken manure with PAM (Polyacrile Amide) to soil aggregate, bulk density and soil permeability rate. The result of this research, were: 1) An incremental addition of chicken manure into soil increased soil aggregation percentage, soil stability and soil permeability rate, and 2) The combined incremental additions of chicken manure with PAM were found to be more effective than only an incremental additions of chicken manure, increasing the aggregation percentage, soil aggregate stability, from the soil one day drainage process, but another case in decreasing the bulk density permeability rate from the soil with the same process.